Roles of pastoral networks for sustainable rangeland management - Fagouri S. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Pastoral resources are deteriorating more and more. One of the causes of degradation is the users’ perception of collective resources, exploiting them with a disregard for others. The rights of pastoral communities are deteriorating further due to the development policies implemented. Pastoral communities have knowledge of rangeland management and need land security as well as policies that take them into consideration. Pastoral policies should involve pastoral communities in decision-making processes related to the sustainable use, development and conservation of pastoral resources, and in pastoral resource planning and management programmes. Networking is one of the essential tools in sustainable management and in sharing knowledge acquired through learning and experience in the development of natural resources. At an international level networking is a powerful channel to disseminate and generalize information to increase awareness of the value that a common resource has for the sustainable management of natural resources by combining ancestral knowledge and modern forms of organization. Networks also make it possible to advocate for pastoral communities and the sustainable management of natural resources. The Arab Network of Pastoral Communities, which was initiated by IUCN West Asia in Amman 2016, brings together civil society organizations, researchers, experts, policymakers and other stakeholders.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)